Superstrutures above the Periodic Law (About the article of O.V. Mikhailov) - I. S. Dmitriev (Высшее образование в России, 2019)
The author expresses critical remarks regarding the article by O.V. Mikhailov on teaching the topic “Mendeleev’s Periodic law” by at the national research University. Some specific errors of O.V. Mikhailov relating to historical-scientific and quantum-chemical issues are indicated. The article also presents a general critical assessment of his approach to teaching.